Análisis de la gestión de créditos y cobranzas de la Caja Municipal de Ahorro y Crédito de Maynas S.A., periodo 2015 - 2019 - López Yaringaño, Karina Domitila (2023)
The objective of this research is to observe if the CMAC Maynas had a correct management of credits and collections in the period 2015-2019. The management of credits and collections of a microfinance institution involves making informed decisions about the level of risk to be tolerated and what to do to mitigate the accepted risk. The research is of a Quantitative type, Descriptive level and Non-experimental design. Therefore, once the information regarding all the operations for the 2015-2019 period of the CMAC Maynas and the aggregate of the eleven CMACs represented by the FEPCMAC has been collected, and then of obtaining, analysis and discussion of the results, it is concluded that during the five years analyzed the ROS of the CMAC Maynas (average 8.75%) has been lower than the average obtained by the CMACs represented by the FEPCMAC (average 15.23%). In addition, it was observed that CMAC Maynas direct credit balances have obtained an average annual growth rate of 4.76%; the delinquency rate also increased, going from an average rate of 5.64% in 2015 to 6.81% in 2019; Likewise, the expenses for provisions of the total loan portfolio of CMAC Maynas increased, in 2015 they represented 8.16% while in 2019 they represented 8.97%. As a consequence, during the analyzed period, the average delinquency rate of CMAC Maynas (6.86%) has been higher than that of CMACs represented by FEPCMAC (6.28%).